Vitamin A restriction during finishing benefits beef retail color display life - Daniel, M.J.; Arnett, A.M.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Because the beef industry commonly uses marbling as an indicator of meat palatability, determining the most cost effective methods of increasing quality grade in cattle is a high priority. Previous research showed that weaning calves at around 90 instead of 200 days of age can be beneficial in reducing cow production costs and increasing marbling in feedlot steers. Other studies demonstrated that high levels of vitamin A inhibit development of intramuscular fat. Vitamin A restriction is used commonly in Japanese cattle to increase marbling scores; this stimulated interest in applying this restriction in U.S. beef production systems. However, little research has been conducted to determine the effect that vitamin A restriction might have on other meat quality components. Therefore, our objective was to determine the effects of feeding high and restricted levels of vitamin A to early and traditionally weaned calves during finishing on color display life, lipid oxidation, and sensory attributes of two beef muscles.
Keywords: Beef; Cattle; Marbling; Vitamin A